Internet of Things for 4.0 Industry Revolution - Setiyo Budiyanto; Lukman Medriavin Silalahi (Journal of Innovation and Community Engagement, 2023)
In this training, participants were given an understanding of the IoT (Internet of Things) for the Industrial Revolution 4.0 and were accompanied by instructors to get to know the technology. The approach method is based on research results that have been published in electrical engineering. We CO (Collaborated Overseas) with UTHM (Universiti Tun Hussein Onn Malaysia) in the CS (Community Service) programme, with the aim of providing guest lectures on the advancement of IoT technology and IR (Industry Revolution) 4.0. Thus, the contribution to this CS activity is to support the improvement of the quality of skilled labor from partner participants to be in line with industry needs. Therefore, the leadership of the institution approved and held the IoT for 4.0 IR training. Universitas Mercu Buana through the Institute for Research and Community Service participated in the field of ICT (Information and Communication Technology) with the long-term target of developing wireless sensors and actuators, and computing methods in embedded systems and the cloud. The conclusion of this CS activity is that participants were very enthusiastic about this activity and and gained the benefits of science, as well as an understanding of telecommunications.